Brilliant persuasion : everyday techniques to boost your powers of persuasion - Young, Stephen C. (Management coach) (Brilliant., 2017)
IT WOULD BE WONDERFUL IF YOU COULD ALWAYS ENSURE EVERYONE AGREED WITH YOUR WAY OF THINKING, WOULDN'T IT? You're already aware of how unlikely you are to progress at work, or "make a name for yourself" in life, if you struggle to get your ideas accepted by your prospects, your clients, your team, your boss, or your peers. Have you noticed how for some people it seems effortless, while the rest of us - maybe you, would benefit from a little help? Step by step, Brilliant Persuasion introduces you to a formidable selection of some of the most powerful persuasion techniques used by the most